Augusto Boal - Babbage, Frances (London : Routledge, 2004)
Context for a Theatre of the Oppressed -- Augusto Boal : early years -- In New York -- At the Arena Theatre of Sao Paulo, 1956-71 -- In exile, 1971-86 -- The 1990s : developments in Rio -- Theatre of the Oppressed in the twenty-first century -- Overview -- Key concepts -- The thesis in detail -- Cardboard Citizens : Going--going--gone -- Mind the Gap and SFX Theatre Company : Never again! -- Conclusions -- Fundamentals -- Workshop structure -- Preparation and games -- Images and experience -- Closure.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Boal, Augusto